Synthesis of Gold Nanoparticles Using Ascorbic Acid Bioreductor and Its Effect on Human Blood Pressure - Aisyah Cici Dwi Rahmadhani; Titik Taufikurohmah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Blood pressure is an important factor in the circulatory system and should be within the normal range of 90-140/60-90 mmHg. Blood pressure imbalances, such as hypertension and hypotension, can be caused by an unhealthy lifestyle, poor diet, or chronic illness. These conditions can trigger oxidative stress, which is an imbalance between the production of free radicals and the body's ability to neutralize them. Oxidative stress can damage cells and tissues, including blood vessels. Therefore, antioxidant intake is needed to help prevent further damage and maintain stable blood pressure. One innovative approach in blood pressure management is the use of gold nanoparticles, which have antioxidant activity. This study aims to characterize gold nanoparticles (AuNPs) synthesized using ascorbic acid bioreductors and examine the effect of their injection on human blood pressure. Characterization was performed using UV-Vis and Transmission Electron Microscopy (TEM), showing a maximum wavelength of 523.50 nm and an average particle diameter of 6.45 nm. Gold nanoparticles were injected intravenously at a dose of 200 mL every week. The results of the study indicate that the administration of gold nanoparticles significantly lowers blood pressure, as shown by the Paired T-Test, which shows an average decrease of 12.6 mmHg (95% CI: 5.1–20.1) and a p-value of 0.004. Based on the blood pressure trend graph, it was found that hypertensive volunteers' blood pressure decreased to normal levels, hypotensive volunteers' blood pressure increased to normal levels, and volunteers with normal blood pressure remained stable. Microscopic analysis showed a higher number of white blood cells in hypertensive volunteers compared to volunteers with normal blood pressure.